Occurrence of brown leaf spot of rice in Punjab, its effect on grain yield and its control - and P.S. BAGGA, P.P.S. PANNU*, S.S. CHAHAL, VINEET K. SHARMA, MANDEEP KAUR (Indian Phytopathology, 2006)
Brown leaf spot of rice was monitored in different districts of Punjab state during 2002 and 2003. It was found that the disease was more severe in certain areas of Amritsar , Gurdaspur and Ropar. During 2002, average severity in different districts ranged from 4.12% (Sangrur) to 18.41% (Amritsar). During 2003 higher average severity (12.13%) was recorded in Gurdaspur followed by Amritsar. Different varieties of rice screened during 2000-2003 revealed that varieties of rice viz. PR-116, PR-114 and PR-106 were found to be more susceptible to the disease as these varieties showed higher severity. The values of severity were recorded as 28.41%, 23.13% and 19.57%, respectively on PR 116 , PR 114 and PR-106 during 2002. The severity was comparatively lower on rest of the varieties. The studies on effect of different severity levels on grain yield revealed that loss in grain yield was higher when the severity of the disease was 13.70% or above and loss at severity level of 42.00% was calculated as 34.38%. Out of four fungicides evaluated Tilt 25 EC managed the disease effectively.